Higher concentration of ascorbic acid as a sole induction factor for osteogenesis on MC3T3-E1 cell model - Farinawati Yazid; Ng, Wan Ching; Nur Atmaliya Luchman; Shahrul Hisham Zainal Ariffin; Rohaya Megat Abdul Wahab (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research aimed to investigate the potential of ascorbic acid (Asc) to act independently as an osteogenic induction factor in a murine pre-osteoblast (MC3T3-E1) model. MC3T3-E1 cells were seeded in culture wells and hydroxyapatite scaffold for two-dimensional and three-dimensional analyses respectively. Cell morphology, viability, osteoblast differentiation, and mineralisation potentials of MC3T3-E1 cells were compared between induction of standard (50 μg/mL) and doubled (100 μg/mL) Asc concentrations in growth media. Cells with fibroblast-like morphology became confluent earlier on day 6 in the standard group compared to the doubled group on day 9. Cell viability and differentiation potential were significantly increased in the doubled group (p < 0.01). Mineralisation occurred in the doubled group after 15 days of seeding but no mineralisation was seen in the standard group. Findings were similar in 3D analysis whereby mineralized nodules were seen only in the doubled group. The relative expression of collagen 1(α) and osteocalcin genes were increased in the doubled group than the standard group. Doubling Asc concentration in a growth medium to 100 μg/mL can induce viability, differentiation, and mineralisation of MC3T3-E1 cells. Thus, higher concentration of ascorbic acid can potentially be used as the sole induction factor in osteogenic medium.